Extreme pressure properties investigation of palm olein using four ball tribotester - M. K. A., Mohamed; N. M., Nasir; N. S., Khasi'ie; Rahimah, Jusoh; Nor Hafizah, Moslim; Ezrinda, Mohd Zahidee; Mohd Zuki, Salleh (AIP Publishing, 2012)
In this study, the numerical solution of stagnation point flow over a stretching surface, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature is considered. The transformed boundary layer equations are solved numerically using the Keller box method. Numerical solutions are obtained for the local heat transfer coefficient and the wall temperature. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter and conjugate parameter are analyzed and discussed.